Diagnostic problems of right-sided heart failure patient with cardiomyopathy cirrhosis - Ida Bagus Aditya Nugraha (Neurologico Spinale Medico Chirurgico, 2021)
Heart failure may cause liver damage, known as cardiomyopathy cirrhosis. Conversely, liver disease could also lead to heart failure and cardiovascular abnormalities. Cirrhotic cardiomyopathy is a relatively rare disease. Diagnosis should be found out as early as possible to prevent complications. Unfortunately, epidemiology data of cirrhotic cardiomyopathy is still limited, and the prevalence is still not precisely known. Hence, we reported a case of a young man with the main problem of right-sided heart failure and suspected cardiac cirrhosis with unclear manifestation. This case has a good outcome so that we hope this report could give a great reference on treating cardiomyopathy cirrhosis.